2018
DOI: 10.1002/pon.4686
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of multigene cancer panel testing in patients with a clinical suspicion of hereditary cancer across Spain

Abstract: Our results suggest that patients can psychologically cope with cancer panel testing, but distress and uncertainty observed in carriers of moderate penetrance cancer variants in this cohort warrant further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 34 publications
2
68
3
Order By: Relevance
“…Approximately 16 percent of the participants chose to learn less than all the information available (for example, some chose not to learn the results for genes unrelated to breast or ovarian cancer); these preferences were not related to demographic or self‐reported psychological factors. A similar study of multigene panel testing in Spain also found varying information preferences among participants pursuing testing, with 84 percent preferring to learn VUS results and 92 percent desiring to learn results for moderate‐penetrance genes . Thus, although most individuals appear to prefer to receive all available genetic‐risk information, some hold distinct preferences for receiving only specific types of information.…”
Section: Current Findings Regarding Psychosocial Effects Of Multigenementioning
confidence: 88%
“…Approximately 16 percent of the participants chose to learn less than all the information available (for example, some chose not to learn the results for genes unrelated to breast or ovarian cancer); these preferences were not related to demographic or self‐reported psychological factors. A similar study of multigene panel testing in Spain also found varying information preferences among participants pursuing testing, with 84 percent preferring to learn VUS results and 92 percent desiring to learn results for moderate‐penetrance genes . Thus, although most individuals appear to prefer to receive all available genetic‐risk information, some hold distinct preferences for receiving only specific types of information.…”
Section: Current Findings Regarding Psychosocial Effects Of Multigenementioning
confidence: 88%
“…From our perspective, phenotype‐driven panels with opportunistic testing of BRCA1/2 and MMR genes is a conservative but efficient approach for offering cancer gene susceptibility diagnosis compared to expanded panels. The main reasons to pursue this are related to the uncertainty in cancer risk estimates and/or cancer risk spectrum for some of the genes, which has shown to translate in uncertainty in patients in our setting . In a diagnostic and rapid‐turnover setting, diagnostic laboratories may need to focus on testing the most clinically useful genes.…”
Section: Discussionmentioning
confidence: 99%
“…This adds a piece of complexity to genetic counseling and makes interpretation of results more difficult and time‐consuming for laboratories . All the above factors may increase uncertainty and distress in patients who undergo panel testing …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, links between avoidance and, concerns about hereditary predisposition or worries about personal cancer emerged in women who received a VUS result. The disclosure of an ambiguous test result with a lack of actionability may be difficult to understand, maintain uncertainty and distress and require further counselling to interpret the significance of this result in the context of personal or familial cancer history …”
Section: Discussionmentioning
confidence: 99%